KOMODIFIKASI GELANG BENANG TRIDATU DALAM INDUSTRI PARIWISATA BALI - Sudarmana, Ida Bagus Made; Suka Arjawa, I Gusti Putu Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT   The tri datu bracelet is a three-colored bracelet that is used as a reminder to the people of the greatness of God in Balinese culture, the tri datu bracelet which is supposed to be a sacred object, but today is used as a tourist market commodity.  This makes the tri datu bracelet an interesting research object to study from a sociological point of view.  This study uses Max Weber's theory of rational action to analyze the phenomenon of modern tri datu bracelet sales as a form of rational action taken consciously by the community in economic mobility in the modernization era.    Keywords: Commodification, Tri Datu Bracelet, Tourism Industry